Mapping Foreign Migration to Belgium. The digitization of the index cards of the Belgian Aliens’ Police (1832-1889) - Heynssens, Sarah (TSEG - The Low Countries Journal of Social and Economic History, 2020)
Migration caused a lot of turmoil in recent years. Large numbers of people have travelled to Europe in search of a better life. Governments have fallen and political parties have risen or crashed based on their policies concerning these “migration crises”. But how exceptional are these migration trends when placed in a historical perspective? As the subject of migration proves to be one that is to stay on the political agenda, professionals better have the right numbers to construe the policies that will make up the future of the continent. More so, a historic understanding of migration, how migration now differs or resembles past migration, is crucial to put current movements of people into perspective.